INTRAPLATE TECTONICS: FEEDBACK BETWEEN RADIOACTIVE THERMAL WEAKENING AND CRUSTAL DEFORMATION DRIVEN BY MANTLE LITHOSPHERE INSTABILITIES - Pysklywec R.N.; Beaumont C. (My University, 2004)
Two-dimensional viscous–plastic numerical experiments show that weak radioactive crust may be susceptible to significant tectonic activity by the effect of Rayleigh–Taylor-type instability of the sub-crustal lithosphere below a continental interior. In particular, crust having a localized or regional enrichment of radioactive elements can respond to an underlying mantle lithosphere downwelling by initial subsidence then thickening and uplift owing to the positive feedback among thickening, heating, and weakening. Such models may later undergo orogenic deflation as spontaneous crustal extension/thinning and surface subsidence occur while mantle downwelling continues. Strong homogeneous crust subsides dynamically above mantle downwellings and undergoes essentially no internal deformation. A uniform distribution of radioactive elements through the crust, or a concentration at depth, is much more effective in causing thermal weakening of the crust and subsequent intraplate deformation than with radioactive material concentrated nearer the surface. For wide regions of high heat production in the crust the length scale of the intracrustal tectonic zone is controlled by the width of the mantle downwelling in contrast with narrow heat production regions which control their own length scale. In general, the numerical experiments demonstrate that the presence of radioactive elements may make the crust vulnerable to intraplate tectonic deformation and represent a primary control on the way the strength of the crust evolves during sub-crustal forcing. The results may explain first-order features of intraplate tectonics including the subsidence mechanism for intracontinental basins, orogenic crustal contraction, thickening and surface uplift, and subsequent extension and crustal deflation. The processes have particular implications for regions of high radioactive heat production and juvenile crust which would more likely have a higher concentration of radioactive elements in the lower crust.
Keywords: intraplate tectonics; Rayleigh-Taylor instabilities; radioactive heating; numerical modeling;; mantle lithosphere